Gambaran Pengambilan Keputusan Interviewer dalam Wawancara Kerja - Mukhaira El Akmal; Zulfa Farah Salvani; C Celine; Dessy Monica; Indah Ditha Sari (SAFE-Network, 2023)
This study aims to describe the interviewer's decision making in the job interview process. This study uses a qualitative research method with a case study approach. The main subjects in this study were 5 people who had the characteristics of an interviewer in a company who made a recruitment selection in a company. The results showed that each subject had a different way of making decisions. This happens because of differences in the way interviewers make decisions in job interviews. It can be concluded that an interviewer in making decisions there are various kinds that must be assessed, namely: starting from the criteria, background experience, educational background and accurate biodata are all taken into consideration.